Effects of varying laser trimming geometries on thin film resistors. Issue 1 (6th February 2017) - Alafogianni, Maria; Birkett, Martin; Penlington, Roger
Abstract : Purpose: This paper aims to study the effects of varying laser trim patterns on several performance parameters of thin film resistors such as the temperature coefficient of resistance (TCR) and target resistance value. Design/methodology/approach: The benefits and limitations of basic trim patterns are taken into consideration, and the plunge cut, double plunge cut and the curved L-cut were selected to be modelled and tested experimentally. A computer simulation of the laser trim patterns has been developed for the modelling process of the resistors. The influence of the trim length and resistor dimensions on the TCR performance and resistance value of the resistors is investigated. Findings: It is found that variation in trim length, within the range of 5 to 15 mm, can give significant increases in the TCR of the thin films. Thus, for the plunge cut, TCR can reach up to 11.51 ppm/oC, for the double plunge cut up to 14.34 ppm/oC and for the curved L-cut up to 5.11 ppm/oC. Originality/value: Research on the effects of various laser trimming geometries on the TCR and target resistance accuracy is limited, especially for patterns such as the curved L-cut, which is investigated in this paper.